Dampak Kecemasan dan Lingkungan Kerja terhadap Kepuasan Kerja Karyawan pada Masa Pandemik Covid-19 - Desty Riyani; Indah Rizki Maulia (Reviu Akuntansi, Manajemen, dan Bisnis, 2023)
Purpose: The aim of this research is to find out whether there is a significant impact of anxiety and work environment on employee job satisfaction during the Covid-19 pandemic. Methodology/approach: This study uses a quantitative correlational approach using statistical techniques of multiple linear regression analysis with SPSS for Windows 25.0. Data collected using a questionnaire containing statements presented in the form of a Likert scale. The sampling technique used is saturated sampling technique with a total of fifty respondents who are employees of PT Inovasi Kemasan Digital Indonesia. Results/findings: The results of data processing show that anxiety and the work environment together have a significant impact on job satisfaction. With a coefficient of determination of 0.202, it can be said that 16.8% of the employee job satisfaction variable at PT Inovasi Kemasan Digital Indonesia can be explained by the anxiety and work environment , while the remaining 83.2% is explained by other variables. Limitations: This research was conducted during the Covid-19 pandemic where special conditions occurred, with the presence of a virus that endangered lives and caused anxiety in the community, including workers. This study only analyzes anxiety, work environment and job satisfaction. Contribution: The results of this study can be useful for management science and management practitioners as a reference source of information regarding the impact of anxiety and the work environment on employee job satisfaction during a pandemic crisis.